44‐1: Invited Paper: Photo‐alignment and n‐FFS LCD Technologies with IGZO‐TFT Applied to Generation Eight Factory. Issue 1 (May 2016) - Miyake, Isamu; Asagi, Hiroaki; Shimizu, Masahiro; Matsumoto, Kazuhito; Nishihara, Yusuke; Hashimoto, Yoshito; Matsushita, Tomohisa; Shimada, Shinji; Ito, Yasuhisa
Abstract : We achieved a super low power consuming LCD panel with an n‐FFS mode driven by IGZO‐TFTs at low frequency. In this paper, we report the development of a new photo‐alignment process for n‐FFS, which prevents light‐leakage and mura caused by conventional rubbing processes. In addition, we also developed high reliable liquid crystal and photo‐alignment materials, which reduce flicker in low refresh rate driving. These technologies have already been applied to the Generation Eight factory, and are being adopted to small/middle sized LCDs for smartphones, tablet PCs, notebook PCs and so on.